Penalaran Hukum: Bagaimana Merek Terkenal Diposisikan Melalui Positivisme Hukum - Zakki Adlhiyati; Achmad Achmad (Badan Strategi Kebijakan Hukum, 2023)
Legal protection for well-known mark needs to be examined. Indonesia has tried to conform its legal system with international law, most notably the Paris Convention and the TRIPS Agreement. However, the court's decision indicates that the well-known mark remains unfavourable. This paper aimed to analyse judges' rationale when they rejected a lawsuit against a well-known trademark in Indonesia which was the trademark dispute of